Biodegradable copolyester elastomer BALK, preparation method and application thereof

By developing degradable copolyester elastomers and polyester-type pressure-sensitive adhesives, the problem of poor degradability of traditional pressure-sensitive adhesive materials is solved, efficient biodegradation and excellent bonding performance are achieved, and the needs of green and sustainable development are met.

CN118344570BActive Publication Date: 2025-03-07SHENZHEN JF BIO PRODUCTS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410571929.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-10
Publication Date
2025-03-07
Estimated Expiration
2044-05-10

AI Technical Summary

Technical Problem

The widespread application of existing pressure-sensitive adhesives in packaging and other fields has led to an increase in waste, resulting in environmental pollution and waste of resources, and the degradability of traditional pressure-sensitive adhesive materials is poor, making it difficult to meet the needs of green and sustainable development.

Method used

A degradable copolyester elastomer was developed to improve cohesive strength through the copolymer structure of hard and soft segments, and combined with tackifying resins, etc., to prepare a degradable polyester-type pressure-sensitive adhesive with excellent initial viscosity, sticking strength and high peel strength.

Benefits of technology

It realizes efficient biodegradation of pressure-sensitive adhesives, reduces environmental pollution, meets the dual needs of pressure-sensitive adhesives' bonding and degradation properties, and avoids residual glue after peeling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118344570B_ABST
    Figure CN118344570B_ABST
Patent Text Reader

Abstract

The present invention discloses a biodegradable copolyester elastomer BALK, a preparation method and an application thereof, wherein the biodegradable copolyester elastomer BALK is a copolymer of a degradable hard segment and a degradable soft segment, wherein the hard segment is a carboxyl-terminated polyester, and the soft segment is a non-crystalline carbon dioxide-based polyester diol, wherein the mass ratio of the hard segment is 10-30% by mass, the number average molecular weight of the hard segment is 1100-3000, the number average molecular weight of the soft segment is 2000-3000, and the number average molecular weight of the biodegradable copolyester elastomer BALK is 30000-50000. The degradable polyester pressure-sensitive adhesive containing the biodegradable copolyester elastomer BALK of the present invention can simultaneously take into account excellent initial adhesion, sustained adhesion, high peel strength and high degradation rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of pressure-sensitive adhesive tapes, and in particular, relates to a biodegradable copolyester elastomer BALK, a preparation method and application thereof. Background Art

[0002] With the widespread application of pressure-sensitive adhesives in packaging and other fields, pressure-sensitive adhesive waste is increasing year by year, and the pollution and resource waste caused to the environment are becoming increasingly prominent, becoming an issue that cannot be ignored at present and in the future. To solve this problem, society has to strengthen the research on renewable resources and seek efficient and renewable biomass raw materials to replace non-renewable petroleum products. This is not only an inevitable trend of social development, but also promotes the development of biodegradable pressure-sensitive adhesives, becoming an important direction for the packaging and adhesives industry to move towards green and sustainable development.

[0003] At present, pressure-sensitive adhesive substrates can be prepared using degradable materials, but pressure-sensitive adhesives are still more often made of traditional non-degradable materials, mainly rubber-type, thermoplastic elastomers, acrylates, silicones and polyurethanes. Due to compatibility issues, the added additives of rubber-type adhesives are easy to precipitate, resulting in poor weather resistance and aging resistance. Acrylate copolymer pressure-sensitive adhesives usually contain unreacted acrylate monomers, have a strong smell and are irritating to the human body. Polyurethane pressure-sensitive adhesives are less toxic than the first two, but polyurethane pressure-sensitive adhesives have poor degradability, and residual adhesive is prone to appear after the pressure-sensitive adhesive is peeled off. In recent years, polyester elastomers have also been studied as pressure-sensitive adhesives.

[0004] Patent CN117447954A discloses a degradable hot-melt pressure-sensitive adhesive, which includes the following components by mass: 65 to 85 parts of degradable plastic, 5 to 25 parts of degradable tackifying resin, 1 to 9 parts of degradable plasticizer, 0 to 10 parts of filler, and 1 part of antioxidant, wherein the degradable plastic is one or more of polybutylene succinate, polylactic acid, polyglycolic acid, polybutylene terephthalate-adipate, and polypropylene carbonate, but the examples only tried polybutylene terephthalate-adipate, and the pressure-sensitive adhesive had poor adhesion, retention and degradability.

[0005] Patent CN105802145A discloses a biodegradable thermoplastic elastomer, which is composed of the following components: 20-120 parts of a biodegradable resin, 10-120 parts of a filler, 0.2-5 parts of a coupling agent, 0.03-5 parts of a cross-linking agent, 0.1-10 parts of a co-cross-linking agent, 0.2-10 parts of a lubricant, 5-100 parts of a plasticizer and 0.1-40 parts of a compatibilizer. The biodegradable resin is one or more of polybutylene succinate, polybutylene succinate-adipate, polybutylene adipate-terephthalate, polylactic acid, polypropylene carbonate, polycaprolactone, polyhydroxyalkanoate and polyvinyl alcohol. The embodiments are all single resins, and their performance cannot meet the requirements of pressure-sensitive adhesives.

[0006] CN117384577A discloses a carbon dioxide-degradable pressure-sensitive adhesive material. Diacetyl-L-tartaric anhydride is added to the polymerization reaction of carbon dioxide and epoxide to prepare the carbon dioxide-based degradable pressure-sensitive adhesive material through a ternary polymerization reaction. The pressure-sensitive adhesive made from the material has poor adhesion, retention and degradability.

[0007] Developing a pressure-sensitive adhesive product that meets both adhesive properties and biodegradability has significant application value. Summary of the invention

[0008] Based on this, the present invention aims to overcome at least one defect of the prior art and provide a degradable copolyester elastomer, a degradable polyester pressure-sensitive adhesive and a degradable polyester pressure-sensitive adhesive product. The degradable polyester pressure-sensitive adhesive uses the degradable copolyester elastomer of the present invention as a base resin, combined with a tackifying resin, etc., and can simultaneously take into account excellent initial adhesion, lasting adhesion, high peel strength and high degradation rate. The degradable polyester pressure-sensitive adhesive is used in pressure-sensitive adhesive products, and the pressure-sensitive adhesive products as a whole are degradable.

[0009] The invention provides a degradable copolyester elastomer. The degradable copolyester elastomer is a copolymer of a degradable hard segment and a degradable soft segment, wherein the hard segment is a carboxyl-terminated polyester, and the soft segment is a non-crystalline carbon dioxide-based polyester diol, wherein the mass ratio of the hard segment is 10-30 mass %, the number average molecular weight of the hard segment is 1100-3000, the number average molecular weight of the soft segment is 2000-3000, and the number average molecular weight of the degradable copolyester elastomer is 30000-50000.

[0010] The degradable copolyester elastomer of the present invention comprises a degradable hard segment carboxyl-terminated polyester and a degradable soft segment non-crystalline carbon dioxide-based polyester diol. The soft segment non-crystalline carbon dioxide-based polyester diol is a CO2-based diol, which is derived from a third type of carbon source, has a fast degradation rate and a high degradation rate. Since the soft segment carbon dioxide-based polyester diol used is a non-crystalline diol, it has poor cohesion and cannot be used in the field of pressure-sensitive adhesives. Therefore, a degradable hard segment carboxyl-terminated polyester with a specific molecular weight is introduced to increase its cohesive strength. Since the hard segment is also degradable, the hard segment part can also be degraded, so that the copolyester elastomer obtained by polymerizing the hard segment carboxyl-terminated polyester and the soft segment non-crystalline carbon dioxide-based polyester diol is completely degradable.

[0011] Since the hard segment contains carboxyl groups, it can be used as a physical crosslinking point to form a copolyester elastomer with the soft segment carbon dioxide-based polyester diol, thereby improving the cohesive strength of the overall resin, so that it can be used in the field of pressure-sensitive adhesives to meet the bonding properties of pressure-sensitive adhesives. In order to obtain the required performance, the mass ratio of the hard segment to the elastomer should be more than 10%. As its content increases, the cohesive properties of the copolyester elastomer will increase, but too high a hard segment content will lead to an increase in the degree of phase separation, and then the performance of the elastomer will decrease, causing the subsequent pressure-sensitive adhesive performance to decrease. At the same time, if the hard segment content is too high, the physical entanglement of the elastomer will also increase, and then the degradation rate of the elastomer will decrease, so the mass ratio of the hard segment is controlled below 30%. Specifically, the proportion of the hard segment can be 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26% or 28%.

[0012] In addition, the molecular weight of the hard segment, soft segment, and copolyester elastomer will also affect the performance of the degradable copolyester elastomer. For the hard segment, the higher the molecular weight, the stronger the crystallinity, and the stronger the ability to serve as a physical crosslinking point. In order to meet the performance requirements, the number average molecular weight of the hard segment is above 1100, but the crystallinity caused by the excessively high molecular weight is too strong, which makes the microphase separation degree of the degradable copolyester elastomer too large, which in turn leads to a decrease in the performance of the degradable copolyester elastomer and a decrease in the performance of the subsequent pressure-sensitive adhesive. The number average molecular weight of the hard segment should be controlled below 3000. Specifically, the number average molecular weight of the hard segment can be 1200, 1400, 1600, 1800, 2000, 2200, 2400, 2600, 2800 or 2900. For the soft segment, when the molecular weight is too small, the chain segment is too short, and the degradable copolyester elastomer loses elasticity. Therefore, its number average molecular weight is at least 2000. When the molecular weight is too large, it is equivalent to a decrease in the hard segment content, and the strength of the degradable copolyester elastomer decreases, affecting the subsequent use as a pressure-sensitive adhesive matrix resin. The number average control amount should be controlled below 3000. Specifically, the number average molecular weight of the soft segment can be 2100, 2200, 2300, 2400, 2500, 2600, 2700, 2800 or 2900. For the copolyester elastomer, its molecular weight needs to be above 30000 so as to have the required cohesion, but when the molecular weight is too large, it will lead to poor degradation performance, so it needs to be controlled below 50000. The number average molecular weight of the copolyester elastomer can be 32000, 34000, 36000, 38000, 40000, 42000, 44000, 46000 or 48000.

[0013] The technical scheme controls the molecular weight of the soft and hard segments of the degradable copolyester elastomer, the segment content and the molecular weight of the copolyester as a whole, so that the copolyester elastomer has excellent cohesive strength and degradability, and the degradable polyester pressure-sensitive adhesive also has excellent bonding properties and degradation properties. By mixing the degradable copolyester elastomer with a tackifying resin, a plasticizer, etc., the prepared degradable polyester pressure-sensitive adhesive has excellent initial adhesion, lasting adhesion, high peel strength, and high degradation rate, and it is not easy to have residual adhesive after the pressure-sensitive adhesive is peeled off.

[0014] In one embodiment, the carboxyl-terminated polyester is polymerized from a C3-C7 dibasic acid and a C3-C7 diol.

[0015] In one embodiment, the carboxyl-terminated polyester is polybutylene succinate (PBS), and the non-crystalline carbon dioxide-based polyester diol is polypropylene carbonate diol (PPC). PBS and PPC are novel polymer degradable materials, and the degradation mechanism of PBS is: first, by the hydrolysis of CO bonds, and then further degraded under the action of enzymes. PBS is a crystalline material, which can be used as a physical crosslinking point to form a copolyester elastomer with polycarbonate, thereby improving the cohesive strength of the overall resin, so that it can be applied in the field of pressure-sensitive adhesives to meet the bonding properties of pressure-sensitive adhesives, and the PBS synthetic raw material comes from biomass, which is a second-class carbon source, and the degradation performance is also good. The PPC segment is a CO2-based diol, which comes from a third-class carbon source, has a fast degradation rate, and a high degradation rate.

[0016] The present invention also provides a method for preparing a degradable copolyester elastomer, comprising the following steps: putting 10 to 30 parts by weight of carboxyl-terminated polyester and 70 to 90 parts by weight of non-crystalline carbon dioxide-based polyester diol into a reaction kettle, then heating to 180 to 200° C., adding an ester exchange catalyst in an amount of 0.1 to 0.5 wt % of the total mass of the carboxyl-terminated polyester and the non-crystalline carbon dioxide-based polyester diol, reacting for 2 to 3 hours, then heating to 210 to 230° C. to react for 3 to 4 hours, then vacuum polycondensing for 3 to 6 hours, and cooling to room temperature to obtain the degradable copolyester elastomer.

[0017] In one embodiment, the preparation method of the carboxyl-terminated polyester is as follows: 35 to 45 parts of C3-C7 diol and 55 to 65 parts of C3-C7 dibasic acid are put into a reaction kettle, then the temperature is raised to 160 to 180°C, 0.1 to 0.5 wt% of the total mass of the C3-C7 diol and the C3-C7 dibasic acid is added with an ester exchange catalyst, and the reaction is carried out for 3 to 4 hours, and then the temperature is raised to 180 to 200°C for reaction for 1 to 2 hours, and then the temperature is raised to 200 to 220°C for vacuum polycondensation for 1 to 4 hours, and the carboxyl-terminated polyester is obtained after cooling to room temperature.

[0018] In one embodiment, the C3-C7 diol is 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol; and / or the C3-C7 dibasic acid is succinic acid, glutaric acid or adipic acid.

[0019] In one embodiment, the catalyst is tetrabutyl titanate, tetraisopropyl titanate or p-toluenesulfonic acid.

[0020] In one embodiment, the acid value of the carboxyl terminated polyester is 37.4 mgKOH / g to 112 mgKOH / g.

[0021] In one embodiment, the non-crystalline carbon dioxide-based polyester diol has a hydroxyl value of 28.05 mgKOH / g to 56.1 mgKOH / g.

[0022] In one embodiment, during the preparation of the carboxyl-terminated polyester, the amount of the transesterification catalyst used is 0.2 to 0.5 wt % of the total mass of the C3-C7 diol and the C3-C7 dibasic acid.

[0023] The present invention also provides a degradable polyester pressure-sensitive adhesive, characterized in that it comprises the following components calculated in parts by mass:

[0024] 50-60 parts of the above-mentioned degradable copolyester elastomer;

[0025] 40-50 parts of tackifying resin;

[0026] 3-10 parts of plasticizer;

[0027] Antioxidant 0.1-0.2 parts.

[0028] In one embodiment, the tackifying resin is one or more of rosin, hydrogenated rosin, disproportionated rosin, esterified rosin, C5 petroleum resin, C9 petroleum resin, and terpene resin.

[0029] In one embodiment, the plasticizer is one or more of epoxidized soybean oil, linseed oil, castor oil, and palm oil.

[0030] In one embodiment, the antioxidant is one or more of tris(2,4-di-tert-butylphenyl)phosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, di(tridecanol)thiodipropionate, and pentaerythritol tetrakis{3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.

[0031] The present invention also provides a method for preparing a degradable polyester pressure-sensitive adhesive, comprising the following steps: mixing the components of the degradable polyester pressure-sensitive adhesive, stirring at 100° C.-180° C. for 0.1-100 h, and then cooling to obtain the degradable polyester pressure-sensitive adhesive.

[0032] In one embodiment, the mixture is stirred at 120° C.-140° C. for 2-5 hours, and / or the solid content of the solution is 15-25 wt %, and / or a solvent is added after cooling to obtain a degradable pressure-sensitive adhesive solution.

[0033] The present invention also provides a degradable pressure-sensitive adhesive product, comprising a substrate and a pressure-sensitive adhesive layer attached to the substrate, wherein the pressure-sensitive adhesive layer comprises the above-mentioned degradable polyester pressure-sensitive adhesive or the degradable polyester pressure-sensitive adhesive prepared by the above-mentioned preparation method.

[0034] In one embodiment, the substrate is selected from paper, textiles, non-woven fabrics, polymers, metals or wood, and the substrate is preferably one of cellulose film, PET film or paper.

[0035] In one embodiment, the pressure-sensitive adhesive layer has a thickness of 10 to 30 μm.

[0036] In one embodiment, the degradable pressure-sensitive adhesive product is a tape, a glue stick or a film roll.

[0037] In one embodiment, the ball number of the initial adhesion of the degradable pressure-sensitive adhesive product is 7 or more, specifically 8, 9, 10 or more.

[0038] In one embodiment, the 180° peel strength of the degradable pressure-sensitive adhesive product is above 3.6 N / 25 mm, and can also be above 4.0 N / 25 mm, preferably above 5.0 N / 25 mm, more preferably above 6.0 N / 25 mm, above 7.0 N / 25 mm, above 8.0 N / 25 mm, or above 9.0 N / 25 mm.

[0039] In one embodiment, the lasting adhesive force of the degradable pressure-sensitive adhesive product is more than 48 hours, and can also be more than 72 hours.

[0040] In one embodiment, the degradation rate of the degradable pressure-sensitive adhesive product is above 88%, above 90%, or above 92%.

[0041] In one embodiment, the peel strength of the degradable pressure-sensitive adhesive product after aging is greater than 2.8 N / 25 mm, and can also be greater than 3.5 N / 25 mm, greater than 4.2 N / 25 mm, greater than 5.0 N / 25 mm, greater than 6.0 N / 25 mm, or greater than 7.0 N / 25 mm.

[0042] The present invention also provides a method for preparing a degradable pressure-sensitive adhesive product, comprising the following steps:

[0043] (1) mixing the components of the degradable polyester pressure-sensitive adhesive, stirring at 100° C. to 180° C. for 0.1 to 100 h, and then cooling to obtain the degradable pressure-sensitive adhesive;

[0044] (2) coating the degradable pressure-sensitive adhesive on the substrate and keeping the temperature at 75-85° C. for 5-15 minutes to obtain a degradable pressure-sensitive adhesive product.

[0045] The beneficial effects of the present invention are as follows: the degradable copolyester elastomer of the present invention comprises a degradable hard segment carboxyl-terminated polyester and a degradable soft segment non-crystalline carbon dioxide-based polyester diol; since both the hard and soft segments of the polymerized chain segments are degradable, the obtained copolyester elastomer is also completely degradable; the hard segment contains a carboxyl group, which can be used as a physical crosslinking point to form a copolyester elastomer with the soft segment non-crystalline carbon dioxide-based polyester diol, thereby improving the cohesive strength of the overall resin, so that it can be used in the field of pressure-sensitive adhesives to meet the bonding performance of pressure-sensitive adhesives; further, by controlling the molecular weight, segment content and overall molecular weight of the soft and hard segments of the degradable copolyester elastomer, the copolyester elastomer can have excellent cohesive strength and degradability, and the degradable polyester-type pressure-sensitive adhesive has excellent bonding performance and degradation performance at the same time; by mixing the degradable copolyester elastomer with a tackifying resin, a plasticizer and the like, the prepared degradable polyester-type pressure-sensitive adhesive has excellent initial adhesion, lasting adhesion, high peel strength, and high degradation rate, and it is not easy to have residual adhesive after the pressure-sensitive adhesive is peeled off. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 This is the infrared spectrum of the degradable copolyester elastomer of Example 1. DETAILED DESCRIPTION

[0047] The embodiments of the present invention are only used for illustrative description and should not be construed as limiting the present invention.

[0048] For simplicity, only some numerical ranges are explicitly disclosed herein. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range, and any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, although not explicitly stated, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unambiguous range.

[0049] The above application content of the present application is not intended to describe each disclosed embodiment or each implementation in the present application. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each example, enumeration is only used as a representative group and should not be interpreted as exhaustive.

[0050] The polypropylene carbonate diol used in the following examples is from Guangzhou Dazhi Chemical Co., Ltd.

[0051] Unless otherwise specified, the raw materials used in the following examples are common commercially available products.

[0052] The acid value determination method of the following examples is as follows: a suitable amount of sample is fully dissolved in 25 mL of chloroform solution, phenolphthalein is used as an indicator, and 0.1 mol / L potassium hydroxide / ethanol standard solution is used to titrate until it turns red and remains unchanged for 30 seconds.

[0053] The acidity value X of the sample is calculated according to formula (1):

[0054]

[0055] Wherein, 56.1 is the molar mass of potassium hydroxide (g / mol); X represents the acid value of the sample (mgKOH / g); V1 is the milliliters of the potassium hydroxide ethanol standard solution before titration (mL); V2 is the milliliters of the potassium hydroxide ethanol standard solution after titration (mL); C is the concentration of the potassium hydroxide ethanol standard solution (mol / L); and m is the weight of the titrated sample (g).

[0056] The number average molecular weight of the following examples is determined as follows:

[0057] GPC test method: The test was carried out using a GPC instrument of model WATERS1515 from Water Company, USA, with tetrahydrofuran (THF) as the mobile phase, a flow rate of 0.1 mL / min, and monodisperse polystyrene as the molecular weight correction standard.

[0058] Example 1

[0059] A degradable polyester pressure-sensitive adhesive, comprising the following components calculated by mass:

[0060] 50 parts of biodegradable copolyester elastomer;

[0061] 45 parts of tackifying resin rosin;

[0062] Plasticizer: epoxidized soybean oil 5 parts;

[0063] Antioxidant tris(2,4-di-tert-butylphenyl)phosphite 0.15 parts;

[0064] Among them, the degradable copolyester elastomer is a copolymer of degradable carboxyl-terminated polybutylene succinate and degradable polypropylene carbonate diol, wherein the chain segment proportion of carboxyl-terminated polybutylene succinate is about 18%, the number average molecular weight of carboxyl-terminated polybutylene succinate is about 1600, the number average molecular weight of polypropylene carbonate diol is about 2500, and the number average molecular weight of the degradable copolyester elastomer is about 35000.

[0065] The preparation process of the degradable copolyester elastomer is as follows:

[0066] (1) Preparation of hard segment carboxyl-terminated polybutylene succinate

[0067] 40 parts of 1,4-butanediol and 60 parts of succinic acid were put into a reactor, then heated to 165°C, and 0.3wt% of the total mass of 1,4-butanediol and succinic acid was added to the catalyst tetrabutyl titanate, and then reacted for about 3 hours, and then heated to 180°C for about 1 hour, and then heated to 205°C for vacuum polycondensation for 2 hours, and the acid ester was tested. The acid value was tested to be 70.125mgKOH / g (the calculated number average molecular weight was 1600, and the calculation formula was: wherein y is an acid value), and after cooling to room temperature, carboxyl-terminated polybutylene succinate is obtained.

[0068] (2) Preparation of copolyester elastomer

[0069] 18 parts of carboxyl-terminated polybutylene succinate and 82 parts of soft segment non-crystalline carbon dioxide-based polyester diol (polypropylene carbonate diol, molecular weight of about 2500, hydroxyl value of about 44.88 mgKOH / g) were put into a reactor, then heated to 180°C, 0.2wt% of the total mass of carboxyl-terminated polybutylene succinate and non-crystalline carbon dioxide-based polyester diol catalyst tetrabutyl titanate was added, and the reaction was continued for 2 hours, and then the temperature was raised to 220°C for 3 hours, and then vacuum polycondensed for 4 hours, and cooled to room temperature to obtain a degradable copolyester elastomer. The molecular weight of the degradable copolyester elastomer was tested, and the number average molecular weight of the degradable copolyester elastomer was measured to be about 35,000.

[0070] The prepared copolyester elastomer was subjected to infrared testing using a Nicolet iS50 Fourier transform infrared spectrometer from Thermo Fisher Scientific, USA, with a scanning wave number range of 400-4000 cm -1 The number of scans was 32. The sample to be tested was evenly spread on the dried KBr sheet and scanned and tested using a Fourier transform infrared spectrometer.

[0071] Infrared spectrum Figure 1 As shown. Figure 1 It can be seen that at 1740cm -1 With 1262cm -1 The peak at 1378 cm is formed by the (-C=O) bond and (-C=O) bond in the soft segment carbonate bond. -1 The peak at is the -COC- structure of the polyether segment in the soft segment molecular chain. The characteristic peaks of the hard segment are the same as those of the soft segment, so they cannot be seen in infrared.

[0072] Example 2

[0073] A degradable polyester pressure-sensitive adhesive, comprising the following components calculated by mass:

[0074] 50 parts of biodegradable copolyester elastomer;

[0075] 45 parts of tackifying resin rosin;

[0076] Plasticizer: epoxidized soybean oil 5 parts;

[0077] Antioxidant tris(2,4-di-tert-butylphenyl)phosphite 0.15 parts;

[0078] Among them, the degradable copolyester elastomer is a copolymer of degradable carboxyl-terminated polybutylene succinate and degradable polypropylene carbonate diol, wherein the chain segment of carboxyl-terminated polybutylene succinate accounts for about 10%, the number average molecular weight of carboxyl-terminated polybutylene succinate is about 1600, the number average molecular weight of polypropylene carbonate diol is about 2500, and the number average molecular weight of the degradable copolyester elastomer is about 32000.

[0079] The preparation process of the degradable copolyester elastomer is as follows:

[0080] (1) Preparation of hard segment carboxyl-terminated polybutylene succinate: the same as in Example 1.

[0081] (2) Preparation of copolyester elastomer:

[0082] 10 parts of carboxyl-terminated polybutylene succinate and 90 parts of soft segment non-crystalline carbon dioxide-based polyester diol (polypropylene carbonate diol, molecular weight of about 2500, hydroxyl value of about 44.88 mgKOH / g) were put into a reactor, then heated to 190°C, 0.1wt% of the total mass of carboxyl-terminated polybutylene succinate and non-crystalline carbon dioxide-based polyester diol catalyst tetrabutyl titanate was added, and the reaction was carried out for 2 hours, and then the temperature was raised to 210°C for 3 hours, and then vacuum polycondensed for 3 hours, and cooled to room temperature to obtain a degradable copolyester elastomer. The molecular weight of the degradable copolyester elastomer was tested, and the number average molecular weight of the degradable copolyester elastomer was measured to be about 32000.

[0083] Example 3

[0084] A degradable polyester pressure-sensitive adhesive, comprising the following components calculated by mass:

[0085] 50 parts of biodegradable copolyester elastomer;

[0086] 45 parts of tackifying resin rosin;

[0087] Plasticizer: epoxidized soybean oil 5 parts;

[0088] Antioxidant tris(2,4-di-tert-butylphenyl)phosphite 0.15 parts;

[0089] Among them, the degradable copolyester elastomer is a copolymer of degradable carboxyl-terminated polybutylene succinate and degradable polypropylene carbonate diol, wherein the chain segment of carboxyl-terminated polybutylene succinate accounts for about 30%, the number average molecular weight of carboxyl-terminated polybutylene succinate is about 1600, the number average molecular weight of polypropylene carbonate diol is about 2500, and the number average molecular weight of the degradable copolyester elastomer is about 46000.

[0090] The preparation process of the degradable copolyester elastomer is as follows:

[0091] (1) Preparation of hard segment carboxyl-terminated polybutylene succinate: the same as in Example 1.

[0092] (2) Preparation of copolyester elastomer:

[0093] 30 parts of carboxyl-terminated polybutylene succinate and 70 parts of soft segment non-crystalline carbon dioxide-based polyester diol (polypropylene carbonate diol, molecular weight of about 2500, hydroxyl value of about 44.88 mgKOH / g) were put into a reactor, then heated to 200°C, 0.5wt% of the total mass of carboxyl-terminated polybutylene succinate and non-crystalline carbon dioxide-based polyester diol catalyst tetrabutyl titanate was added, and the reaction was carried out for 3 hours, and then the temperature was raised to 230°C for 4 hours, and then vacuum polycondensed for 5.5 hours, and cooled to room temperature to obtain a degradable copolyester elastomer. The molecular weight of the degradable copolyester elastomer was tested, and the number average molecular weight of the degradable copolyester elastomer was measured to be about 46000.

[0094] Example 4

[0095] A degradable polyester pressure-sensitive adhesive, comprising the following components calculated by mass:

[0096] 50 parts of biodegradable copolyester elastomer;

[0097] 45 parts of tackifying resin rosin;

[0098] Plasticizer: epoxidized soybean oil 5 parts;

[0099] Antioxidant tris(2,4-di-tert-butylphenyl)phosphite 0.15 parts;

[0100] Among them, the degradable copolyester elastomer is a copolymer of degradable carboxyl-terminated polybutylene succinate and degradable polypropylene carbonate diol, wherein the chain segment of carboxyl-terminated polybutylene succinate accounts for about 18%, the number average molecular weight of carboxyl-terminated polybutylene succinate is about 1100, the number average molecular weight of polypropylene carbonate diol is about 2000, and the number average molecular weight of the degradable copolyester elastomer is about 34000.

[0101] The preparation process of the degradable copolyester elastomer is as follows:

[0102] (1) Preparation of hard segment polyester:

[0103] 35 parts of 1,4-butanediol and 56 parts of succinic acid were put into a reactor, then heated to 160°C, and 0.2wt% of the total mass of 1,4-butanediol and succinic acid was added as catalyst tetrabutyl titanate, and the reaction was carried out for about 3 hours, and then the temperature was raised to 180°C for about 1 hour, and then the temperature was raised to 200°C for vacuum polycondensation for 1 hour, and the acid ester was tested. The acid value was tested to be 102mgKOH / g (the calculated number average molecular weight was 1100), and carboxyl-terminated polybutylene succinate was obtained after cooling to room temperature.

[0104] (2) Preparation of copolyester elastomer

[0105] 18 parts of carboxyl-terminated polybutylene succinate and 82 parts of soft segment non-crystalline carbon dioxide-based polyester diol (polypropylene carbonate diol, molecular weight of about 2000, hydroxyl value of about 56.1 mgKOH / g) were put into a reactor, then heated to 180°C, 0.2wt% of the total mass of carboxyl-terminated polybutylene succinate and non-crystalline carbon dioxide-based polyester diol catalyst tetrabutyl titanate was added, and the reaction was continued for 2 hours, and then the temperature was raised to 220°C for 3 hours, and then vacuum polycondensed for 3.8 hours, and cooled to room temperature to obtain a degradable copolyester elastomer. The molecular weight of the degradable copolyester elastomer was tested, and the number average molecular weight of the degradable copolyester elastomer was measured to be about 34,000.

[0106] Example 5

[0107] A degradable polyester pressure-sensitive adhesive, comprising the following components calculated by mass:

[0108] 50 parts of biodegradable copolyester elastomer;

[0109] 45 parts of tackifying resin rosin;

[0110] Plasticizer: epoxidized soybean oil 5 parts;

[0111] Antioxidant tris(2,4-di-tert-butylphenyl)phosphite 0.15 parts;

[0112] Among them, the degradable copolyester elastomer is a copolymer of degradable carboxyl-terminated polybutylene succinate and degradable polypropylene carbonate diol, wherein the chain segment of carboxyl-terminated polybutylene succinate accounts for about 18%, the number average molecular weight of carboxyl-terminated polybutylene succinate is about 2000, the number average molecular weight of polypropylene carbonate diol is about 3000, and the number average molecular weight of the degradable copolyester elastomer is about 40000.

[0113] The preparation process of the degradable copolyester elastomer is as follows:

[0114] (1) Preparation of hard segment carboxyl terminated polybutylene succinate:

[0115] 40 parts of 1,4-butanediol and 60 parts of succinic acid were put into a reactor, then heated to 180°C, and 0.3wt% of the total mass of 1,4-butanediol and succinic acid was added as catalyst tetrabutyl titanate, and the reaction was carried out for about 3 hours, and then the temperature was raised to 200°C for about 1 hour, and then the temperature was raised to 205°C for vacuum polycondensation for 2.5 hours, and the acid ester was tested. The acid value was tested to be 56.1mgKOH / g (the calculated number average molecular weight was 2000), and carboxyl-terminated polybutylene succinate was obtained after cooling to room temperature.

[0116] (2) Preparation of copolyester elastomer

[0117] 18 parts of carboxyl-terminated polybutylene succinate and 82 parts of soft segment non-crystalline carbon dioxide-based polyester diol (polypropylene carbonate diol, molecular weight of about 3000, hydroxyl value of about 37.4KOH / g) were put into a reactor, then heated to 180°C, 0.2wt% of the total mass of carboxyl-terminated polybutylene succinate and non-crystalline carbon dioxide-based polyester diol catalyst tetrabutyl titanate was added, and the reaction was continued for 2h, and then the temperature was raised to 220°C for reaction for 3h, and then vacuum polycondensation was performed for 5h, and the degradable copolyester elastomer was obtained after cooling to room temperature. The molecular weight of the degradable copolyester elastomer was tested, and the number average molecular weight of the degradable copolyester elastomer was measured to be about 40000.

[0118] Example 6

[0119] A degradable polyester pressure-sensitive adhesive, comprising the following components calculated by mass:

[0120] 50 parts of biodegradable copolyester elastomer;

[0121] 45 parts of tackifying resin rosin;

[0122] Plasticizer: epoxidized soybean oil 5 parts;

[0123] Antioxidant tris(2,4-di-tert-butylphenyl)phosphite 0.15 parts;

[0124] Among them, the degradable copolyester elastomer is a copolymer of degradable carboxyl-terminated polybutylene succinate and degradable polypropylene carbonate diol, wherein the chain segment of carboxyl-terminated polybutylene succinate accounts for about 18%, the number average molecular weight of carboxyl-terminated polybutylene succinate is about 2900, the number average molecular weight of polypropylene carbonate diol is about 2500, and the number average molecular weight of the degradable copolyester elastomer is about 49000.

[0125] The preparation process of the degradable copolyester elastomer is as follows:

[0126] (1) Preparation of hard segment carboxyl terminated polybutylene succinate:

[0127] 45 parts of 1,4-butanediol and 65 parts of succinic acid were put into a reactor, then heated to 165°C, and 0.5wt% of the total mass of 1,4-butanediol and succinic acid was added as catalyst tetrabutyl titanate, and then reacted for about 4 hours, and then heated to 180°C for about 2 hours, and then heated to 220°C for vacuum polycondensation for 4 hours, and its acid ester was tested. The acid value was tested to be 38.7mgKOH / g (the calculated number average molecular weight was 2900), and carboxyl-terminated polybutylene succinate was obtained after cooling to room temperature.

[0128] (2) 18 parts of hard segment polyester and 82 parts of soft segment non-crystalline CO2-based polyester diol (polypropylene carbonate diol, molecular weight of about 2500, hydroxyl value of about 44.88 mgKOH / g) were put into a reactor, then heated to 180°C, carboxyl-terminated polybutylene succinate and non-crystalline CO2-based polyester diol were added, and 0.2 wt% of the total mass of catalyst tetrabutyl titanate was reacted for 2 hours, then heated to 220°C for 4 hours, then vacuum polycondensed for 6 hours, and cooled to room temperature to obtain a degradable copolyester elastomer. The degradable copolyester elastomer was tested for molecular weight, and the number average molecular weight of the degradable copolyester elastomer was measured to be about 49,000.

[0129] Example 7

[0130] A degradable polyester pressure-sensitive adhesive, comprising the following components calculated by mass:

[0131] 55 parts of degradable copolyester elastomer;

[0132] 40 parts of tackifying resin rosin;

[0133] Plasticizer: 3 parts of epoxidized soybean oil;

[0134] Antioxidant tris(2,4-di-tert-butylphenyl)phosphite 0.1 part;

[0135] The degradable copolyester elastomer is the same as that in Example 1.

[0136] Example 8

[0137] A degradable polyester pressure-sensitive adhesive, comprising the following components calculated by mass:

[0138] 60 parts of biodegradable copolyester elastomer;

[0139] 50 parts of tackifying resin rosin;

[0140] Plasticizer epoxidized soybean oil 10 parts;

[0141] Antioxidant tris(2,4-di-tert-butylphenyl)phosphite 0.2 parts;

[0142] The degradable copolyester elastomer is the same as that in Example 1.

[0143] Example 9

[0144] A degradable polyester pressure-sensitive adhesive, comprising the following components calculated by mass:

[0145] 50 parts of biodegradable copolyester elastomer;

[0146] Tackifying resin C5 petroleum resin 45 parts;

[0147] Plasticizer linseed oil 5 parts;

[0148] Antioxidant: 0.15 parts of di(tridecanol)thiodipropionate.

[0149] The degradable copolyester elastomer is the same as that in Example 1.

[0150] Examples 10 to 18

[0151] A degradable pressure-sensitive adhesive tape comprises a base film and a pressure-sensitive adhesive layer attached to the base film, wherein the components of the pressure-sensitive adhesive layer are the degradable polyester pressure-sensitive adhesives of Examples 1 to 9 respectively, and the base film is a PET film.

[0152] The preparation process of the degradable pressure-sensitive adhesive tape is as follows:

[0153] (1) The components of the degradable polyester pressure-sensitive adhesives of Examples 1 to 9 were mixed respectively, stirred at 130° C. for 3 h, then cooled to room temperature, and then added with chloroform solution to obtain a degradable pressure-sensitive adhesive solution with a solid content of 20 wt %;

[0154] (2) The degradable pressure-sensitive adhesive solution is coated on the base film by a coating machine and kept at 80° C. for 10 min to obtain a degradable pressure-sensitive adhesive tape with a pressure-sensitive adhesive layer thickness of about 15 μm.

[0155] Embodiment 19

[0156] A degradable pressure-sensitive adhesive tape comprises a base film and a pressure-sensitive adhesive layer attached to the base film, wherein the pressure-sensitive adhesive layer is made of the degradable polyester pressure-sensitive adhesive of Example 1, and the base film is a PET film.

[0157] The preparation process of the degradable pressure-sensitive adhesive tape is as follows:

[0158] (1) The components of the degradable polyester pressure-sensitive adhesive of Example 1 were mixed, stirred at 120° C. for 5 h, then cooled to room temperature, and then ethyl acetate was added to obtain a degradable pressure-sensitive adhesive solution with a solid content of 15 wt %;

[0159] (2) The degradable pressure-sensitive adhesive solution is coated on the base film by a coating machine and kept at 75° C. for 15 min to obtain a degradable pressure-sensitive adhesive tape with a pressure-sensitive adhesive layer thickness of about 30 μm.

[0160] Embodiment 20

[0161] A degradable pressure-sensitive adhesive tape comprises a base film and a pressure-sensitive adhesive layer attached to the base film, wherein the components of the pressure-sensitive adhesive layer are the degradable polyester pressure-sensitive adhesive of Example 1, and the base film is a cellulose film.

[0162] The preparation process of the degradable pressure-sensitive adhesive tape is as follows:

[0163] (1) The components of the degradable polyester pressure-sensitive adhesive of Example 1 were mixed, stirred at 140° C. for 2 h, then cooled to room temperature, and then xylene was added to obtain a degradable pressure-sensitive adhesive solution with a solid content of 25 wt %;

[0164] (2) The degradable pressure-sensitive adhesive solution is coated on the base film by a coating machine and kept at 85° C. for 5 minutes to obtain a degradable pressure-sensitive adhesive tape with a pressure-sensitive adhesive layer thickness of about 10 μm.

[0165] Comparative Example 1

[0166] A pressure-sensitive adhesive tape, whose components and preparation process are basically the same as those of Example 10, except that the copolyester elastomer is different. The molecular weight of the copolyester elastomer in this comparative example is about 25,000.

[0167] Among them, the preparation process of copolyester elastomer is as follows:

[0168] 18 parts of carboxyl-terminated polybutylene succinate and 82 parts of soft segment non-crystalline carbon dioxide-based polyester diol (polypropylene carbonate diol, molecular weight of about 2500, hydroxyl value of about 44.88 mgKOH / g) were put into a reactor, then heated to 180°C, 0.2wt% of the total mass of carboxyl-terminated polybutylene succinate and non-crystalline carbon dioxide-based polyester diol catalyst tetrabutyl titanate was added, and the reaction was continued for 2 hours, and then the temperature was raised to 220°C for 3 hours, and then vacuum polycondensed for 2 hours, and cooled to room temperature to obtain a degradable copolyester elastomer. The molecular weight of the degradable copolyester elastomer was tested, and the number average molecular weight of the degradable copolyester elastomer was measured to be about 25000, wherein the preparation of the carboxyl-terminated polybutylene succinate was the same as that of Example 1.

[0169] Comparative Example 2

[0170] A pressure-sensitive adhesive tape, whose components and preparation process are basically the same as those of Example 10, except that the copolyester elastomer is different. The molecular weight of the copolyester elastomer in this comparative example is about 56,000.

[0171] Among them, the preparation process of copolyester elastomer is as follows:

[0172] 18 parts of carboxyl-terminated polybutylene succinate and 82 parts of non-crystalline carbon dioxide-based polyester diol (polypropylene carbonate diol, molecular weight of about 2500, hydroxyl value of about 44.88mgKOH / g) were put into a reactor, then heated to 180°C, 0.2wt% of the total mass of carboxyl-terminated polybutylene succinate and non-crystalline carbon dioxide-based polyester diol catalyst tetrabutyl titanate was added, and the reaction was continued for 2h, and then the temperature was raised to 240°C for 3h, and then vacuum polycondensed for 7h, and cooled to room temperature to obtain a degradable copolyester elastomer. The molecular weight of the degradable copolyester elastomer was tested, and the number average molecular weight of the degradable copolyester elastomer was measured to be about 56000, wherein the preparation of the carboxyl-terminated polybutylene succinate was the same as that of Example 1.

[0173] Comparative Example 3

[0174] A pressure-sensitive adhesive tape, whose components and preparation process are basically the same as those of Example 10, except that the copolyester elastomer is different. In the copolyester elastomer of this comparative example, the polybutylene succinate segment accounts for 35%.

[0175] The preparation process of the copolyester elastomer is as follows:

[0176] The preparation process is as follows: 35 parts of carboxyl-terminated polybutylene succinate and 65 parts of soft segment carbon dioxide-based polyester diol (polypropylene carbonate diol, molecular weight of about 2500, hydroxyl value of about 44.88 mgKOH / g) are put into a reactor, then the temperature is raised to 180°C, 0.2wt% of the total mass of carboxyl-terminated polybutylene succinate and non-crystalline carbon dioxide-based polyester diol catalyst tetrabutyl titanate is added, and the reaction is carried out for 2 hours, and then the temperature is raised to 220°C for reaction for 3 hours, and then vacuum polycondensation is carried out for 4 hours, and the degradable copolyester elastomer is obtained after cooling to room temperature. The molecular weight of the degradable copolyester elastomer is tested, and the number average molecular weight of the degradable copolyester elastomer is measured to be about 36000, wherein the preparation of the carboxyl-terminated polybutylene succinate is the same as that of Example 1.

[0177] Comparative Example 4

[0178] A pressure-sensitive adhesive tape, whose components and preparation process are basically the same as those of Example 10, except that the copolyester elastomer is different. The number average molecular weight of the polybutylene succinate segment in the copolyester elastomer of this comparative example is 1000.

[0179] The preparation process of the copolyester elastomer is as follows:

[0180] (1) Preparation of hard segment carboxyl terminated polybutylene succinate:

[0181] 40 parts of 1,4-butanediol and 55 parts of succinic acid were put into a reactor, then heated to 165°C, and 0.3wt% of the total mass of 1,4-butanediol and succinic acid was added as catalyst tetrabutyl titanate, and then reacted for about 3 hours, and then heated to 180°C for about 1 hour, and then heated to 205°C for vacuum polycondensation for 40 minutes, and the acid ester was tested. The acid value was tested to be 112mgKOH / g (the calculated number average molecular weight was 1000), and carboxyl-terminated polybutylene succinate was obtained after cooling to room temperature.

[0182] (2) Preparation of copolyester elasticity: basically the same as Example 10, except that the carboxyl-terminated polybutylene succinate used is different.

[0183] Comparative Example 5

[0184] A pressure-sensitive adhesive tape, whose components and preparation process are basically the same as those of Example 10, except that the copolyester elastomer is different, and the number average molecular weight of the copolymer of carbon dioxide-based polyester diol in this comparative example is 1500. The difference between its preparation process and that of Example 10 is that the number average molecular weight of the copolymer of carbon dioxide-based polyester diol selected is 1500.

[0185] Comparative Example 6

[0186] A pressure-sensitive adhesive tape, whose components and preparation process are basically the same as those of Example 10, except that the copolyester elastomer is different, and the soft segment of the copolyester elastomer in this comparative example is polytetramethylene furan ether diol. The difference between its preparation process and that of Example 1 is that the soft segment diol selected is polytetramethylene furan ether diol, with a molecular weight of about 2500, brand PTMG-2500, sourced from Shanghai Kaiyin Chemical Co., Ltd.

[0187] Comparative Example 7

[0188] A pressure-sensitive adhesive tape, the components and preparation process of which are basically the same as those of Example 10, except that the copolyester elastomer is different, and the copolymer of the carbon dioxide-based polyester diol in this comparative example is a crystalline polymer. The difference between the preparation process and that of Example 1 is that the copolymer of the carbon dioxide-based polyester diol selected is a crystalline polymer with a molecular weight of about 2500, a brand of UM90 (polycarbonate diol), and is from Ube Corporation of Japan.

[0189] Comparative Example 8

[0190] A pressure-sensitive adhesive tape, whose components and preparation process are basically the same as those of Example 10, except that the elastomer is different. The elastomer of this comparative example 1 is a carbon dioxide-based polyester polyurethane elastomer.

[0191] The preparation of carbon dioxide based polyester polyurethane elastomer:

[0192] 125g of carbon dioxide-based polyester diol (polypropylene carbonate diol, molecular weight of about 2500, hydroxyl value of about 44.88mgKOH / g) is put into a reactor, then the temperature is raised to 80°C, 0.2wt% of the catalyst tin isooctanoate by mass of the carbon dioxide-based polyester diol is added and stirred for 5 minutes, 5.6g of diphenylmethane diisocyanate is added and reacted for 3h, and a degradable carbon dioxide-based polyester polyurethane elastomer is obtained after cooling to room temperature. The molecular weight of the degradable polyurethane elastomer is tested, and the molecular weight of the degradable polyurethane elastomer is measured to be about 35000.

[0193] The performance tests were conducted on the degradable pressure-sensitive adhesive tapes of Examples 10 to 20 and the pressure-sensitive adhesive tapes of Comparative Examples 1 to 8. The test items included:

[0194] (1) Initial adhesion: Tested according to Method A in GB / T 4852-2002, with the slope inclined at 30°.

[0195] (2) 180° peel strength: Tested according to GB / T 2792

[0196] (3) Adhesion: The test was conducted in accordance with the provisions of Method A in GB / T 4851-2014. The width of the degradable tape sample was 25 mm, the length of the adhesive surface between the sample and the steel plate was (12 ± 0.5 mm), and the mass of the weight was (1000 ± 5 g).

[0197] (4) Biodegradability: Tested in accordance with the requirements of GB / T 19277.1.

[0198] (5) Aging resistance: The tape was placed in a constant temperature and humidity aging box at 70°C and 95% humidity for 72 hours, and then the peel strength was measured.

[0199] The test results are shown in Table 1.

[0200] Table 1

[0201]

[0202]

[0203] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the technical solution of the present invention, and are not intended to limit the specific implementation methods of the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the claims of the present invention shall be included in the protection scope of the claims of the present invention.

Claims

1. A degradable copolyester elastomer, characterized in that: The degradable copolyester elastomer is a copolymer of a degradable hard segment and a degradable soft segment, wherein the hard segment is a carboxyl-terminated polyester, and the soft segment is a non-crystalline carbon dioxide-based polyester diol, wherein the mass ratio of the hard segment is 12-30% by mass, the number average molecular weight of the hard segment is 1100-3000, the number average molecular weight of the soft segment is 2000-3000, the number average molecular weight of the degradable copolyester elastomer is 30000-50000, and the degradable polyester pressure-sensitive adhesive prepared by mixing the degradable copolyester elastomer with a tackifying resin and a plasticizer has an initial adhesion ball number of 7-10, a 180° peel strength of 3.6N / 25mm-8.8N / 25mm, a degradation rate of 88%-92%, and a peel strength after aging of 3.5N / 25mm-7.0N / 25mm.

2. The degradable copolyester elastomer according to claim 1, characterized in that: The number average molecular weight of the carboxyl-terminated polyester is 1200-2900; and / or the number average molecular weight of the degradable copolyester elastomer is 30000-40000.

3. The degradable copolyester elastomer according to claim 1, characterized in that: The carboxyl-terminated polyester is polymerized from a C3-C7 dibasic acid and a C3-C7 diol.

4. The degradable copolyester elastomer according to claim 1, characterized in that: The carboxyl-terminated polyester is polybutylene succinate, and the non-crystalline carbon dioxide-based polyester diol is polypropylene carbonate diol.

5. The degradable copolyester elastomer according to claim 1, characterized in that: The degradable polyester pressure-sensitive adhesive has a lasting adhesive force of more than 48 hours.

6. A method for preparing a degradable copolyester elastomer according to any one of claims 1 to 5, characterized in that: The steps include: 10 to 30 parts by weight of carboxyl-terminated polyester and 70 to 90 parts by weight of non-crystalline carbon dioxide-based polyester diol are put into a reaction kettle, then the temperature is raised to 180 to 200° C., 0.1 to 0.5 wt% of the total mass of the carboxyl-terminated polyester and the non-crystalline carbon dioxide-based polyester diol is added with an ester exchange catalyst, and the reaction is carried out for 2 to 3 hours, and the temperature is then raised to 210 to 230° C. to react for 3 to 4 hours, followed by vacuum polycondensation for 3 to 6 hours, and the degradable copolyester elastomer is obtained after cooling to room temperature.

7. The preparation method according to claim 6, characterized in that: The preparation method of the carboxyl-terminated polyester is as follows: 35 to 45 parts of C3-C7 diol and 55 to 65 parts of C3-C7 dibasic acid are put into a reaction kettle, then the temperature is raised to 160 to 180° C., 0.1 to 0.5 wt% of the total mass of the C3-C7 diol and the C3-C7 dibasic acid is added with an ester exchange catalyst, and the reaction is carried out for 3 to 4 hours, and then the temperature is raised to 180 to 200° C., and the reaction is carried out for 1 to 2 hours, and then the temperature is raised to 200 to 220° C., vacuum polycondensation is carried out for 1 to 4 hours, and the carboxyl-terminated polyester is obtained after cooling to room temperature.

8. The preparation method according to claim 7, characterized in that: The C3-C7 diol is 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol; and / or, the C3-C7 dibasic acid is succinic acid, glutaric acid or adipic acid; and / or, the catalyst is tetrabutyl titanate, tetraisopropyl titanate or p-toluenesulfonic acid.

9. A degradable polyester pressure-sensitive adhesive, characterized in that: It includes the following components calculated by mass: 50-60 parts of the degradable copolyester elastomer according to any one of claims 1 to 5; 40-50 parts of tackifying resin; 3 to 10 parts of plasticizer; Antioxidant 0.1-0.2 parts.

10. The degradable polyester pressure-sensitive adhesive according to claim 9, characterized in that: The tackifying resin is one or more of natural rosin, hydrogenated rosin, disproportionated rosin, esterified rosin, C5 petroleum resin, C9 petroleum resin and terpene resin.

11. The degradable polyester pressure-sensitive adhesive according to claim 9, characterized in that: The plasticizer is one or more of epoxidized soybean oil, linseed oil, castor oil and palm oil.

12. The degradable polyester pressure-sensitive adhesive according to claim 9, characterized in that: The antioxidant is one or more of tris(2,4-di-tert-butylphenyl)phosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, di(tridecanol)thiodipropionate, and tetrakis{3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate}pentaerythritol.

13. A method for preparing the degradable polyester pressure-sensitive adhesive according to any one of claims 9 to 12, characterized in that: The method comprises the following steps: mixing various components of the degradable polyester pressure-sensitive adhesive, stirring at 100-180° C. for 0.1-100 hours, and then cooling to obtain the degradable polyester pressure-sensitive adhesive.

14. The method for preparing the degradable polyester pressure-sensitive adhesive according to claim 13, characterized in that: The mixture is stirred at 120° C.-140° C. for 2-5 hours, and / or the solid content of the solution is 15-25 wt %, and / or a solvent is added after cooling to obtain a degradable pressure-sensitive adhesive solution.

15. A degradable pressure-sensitive adhesive product, characterized in that: It comprises a substrate and a pressure-sensitive adhesive layer attached to the substrate, wherein the pressure-sensitive adhesive layer comprises the degradable polyester pressure-sensitive adhesive according to any one of claims 9 to 12, or the degradable polyester pressure-sensitive adhesive prepared by the preparation method of any one of claims 13 to 14.

16. The degradable pressure-sensitive adhesive product according to claim 15, characterized in that: The substrate is selected from paper, textiles, non-woven fabrics, polymers, metals or wood, and / or the thickness of the pressure-sensitive adhesive layer is 10 to 30 μm.

17. The degradable pressure-sensitive adhesive product according to claim 15, characterized in that: The substrate is one of cellulose film, PET film or paper.

18. The degradable pressure-sensitive adhesive product according to claim 15, characterized in that: The degradable pressure-sensitive adhesive product is an adhesive tape, an adhesive stick or a film roll.

19. The degradable pressure-sensitive adhesive product according to claim 15, characterized in that: The initial adhesion of the degradable pressure-sensitive adhesive product is 7-10, the 180° peel strength is 3.6N / 25mm-8.8N / 25mm, the degradation rate is 88%-92%, and the peel strength after aging is 3.5N / 25mm-7.0N / 25mm 20. The degradable pressure-sensitive adhesive product according to claim 15, characterized in that: The lasting adhesion of the biodegradable polyester pressure-sensitive adhesive product is more than 48 hours.

21. A method for preparing a degradable pressure-sensitive adhesive product according to any one of claims 15 to 20, characterized in that: The steps include: (1) mixing the components of the degradable polyester pressure-sensitive adhesive, stirring at 100° C. to 180° C. for 0.1 to 100 h, and then cooling to obtain the degradable pressure-sensitive adhesive; (2) coating the degradable pressure-sensitive adhesive on the substrate and keeping the temperature at 75-85° C. for 5-15 minutes to obtain a degradable pressure-sensitive adhesive product.

Citation Information

Patent Citations

  • Biodegradable thermoplastic elastomer and production method thereof

    CN105802145A

  • Degradable pressure-sensitive adhesive material based on carbon dioxide as well as preparation method and application of degradable pressure-sensitive adhesive material

    CN117384577A

  • Poly(alkene carbonate) diol-polybutylene succinate copolymer and preparation method thereof

    CN101735434A

  • Poly(alkene carbonate)diol-poly(butylene succinate) copolymer and preparation method thereof

    CN102241814A

  • Preparation method of aliphatic polyester-b-polycarbonate block biodegradable polyester

    CN107141459A